2015
DOI: 10.1186/s12891-015-0578-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of three landmarking methods for dual inclinometry measurements of lumbar flexion and extension

Abstract: BackgroundTo examine the intra and inter-rater reliability of lumbar flexion and extension measurements attained using three landmarking methods for dual inclinometry.MethodsThis was a repeated measures reliability study. Convenience sampling was used to obtain forty volunteer subjects. Two assessors measured a series of lumbar flexion and extension movements using the J-Tech™ dual inclinometer. Three different landmarking methods were used: 1) straight palpation of PSIS and L1, 2) palpation of PSIS and the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…Schober’s test for assessment of the range of motion, i.e. lumbar spine flexion was made by the researcher [14]. Schober’s test was measured before, after the two-week treatment and after 3 months follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Schober’s test for assessment of the range of motion, i.e. lumbar spine flexion was made by the researcher [14]. Schober’s test was measured before, after the two-week treatment and after 3 months follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…An Acumar digital inclinometer was used to assess ROM (see Figure 2 ) at the cervical spine (Csp). Digital inclinometry (DI) has been previously used in several trials assessing cervical, thoracic and lumbar spine ROM where all authors concluded moderate to good inter-rater reliability (ICC = 0.6–0.9) ( Prushansky et al, 2010 ; MacDermid et al, 2014 , 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…All anatomical landmarks were palpated by the examiner, with the subject in upright standing, consistent with established techniques. [2][3][4]6,8 In one measurement, the landmarks were the palpated T12 spinous process and the palpated S2 region. In the other measurement, the landmarks were the palpated S2 region and 15-cm cephalad to it.…”
Section: Methodsmentioning
confidence: 99%